Kemampuan Komunikasi pada Anak dengan Indikasi Keterlambatan Perkembangan Kognitif Usia 5-6 Tahun di RA Az-Zahra - Nurazizah Nurazizah; Sima Mulyadi; Risbon Sianturi (Universitas Pendidikan Indonesia (UPI), 2023)
Communication skills are important to have from an early age because with communication each individual is able to build social interactions to maintain life. According to the theory of cognitivism, it states that there is a relationship between an individual’s cognitive abilities and language development, one of which is communication skills. Therefore, this study aims to determine the communication skills of children who are indicated to have delayed cognitive development aged 5-6 years in RA Az-Zahra, Sukarame Village, Sukarame District, Tasikmalaya Regency. This study uses a qualitative approach with case study research methods. The results of this study indicate that the communication skills of children who are indicated to have delayed cognitive development aged 5-6 years have not been able to achieve communication skills based on the characteristics of communication skills that children aged 5-6 years should have. In conclusion, the data obtained include credible data because between the cognitivism theory that is the reference and the research data there are similarities that an individual’s cognitive development affects language development, especially an individual’s communication skills. Kemampuan komunikasi merupakan hal yang penting dimiliki sejak usia dini karena dengan komunikasi setiap individu mampu membangun interaksi sosial untuk mempertahankan kehidupan. Menurut teori kognitivisme menyatakan bahwa terdapat hubungan antara kemampuan kognitif seorang idnividu dengan perkembangan bahasanya, salah satunya kemampuan komunikasi. Maka dari itu penelitian ini bertujuan untuk mengetahui kemampuan komunikasi pada anak yang terindikasi mengalami keterlambatan perkembangan kognitif usia 5-6 tahun di RA Az-Zahra Desa Sukarame Kecamatan Sukarame Kabupaten Tasikmalaya. Penelitian ini menggunakan pendekatan kualitatif dengan metode penelitian studi kasus. Hasil penelitian ini menunjukkan bahwa kemampuan komunikasi pada anak yang terindikasi mengalami keterlambatan perkembangan kognitif usia 5-6 tahun belum mampu mencapai kemampuan komunikasi berdasarkan karakteristik kemampuan komunikasi yang seharusnya dimiliki anak usia 5-6 tahun. Kesimpulannya data yang didapatkan termasuk data kredibel karena antara teori kognitivisme yang menjadi rujukan dan data hasil penelitian terdapat kesamaan bahwa pekembangan kognitif seorang individu mampengaruhi terhadap perkembangan bahasa khsusunya kemampuan komunikasi seorang individu.